2003
DOI: 10.1038/nature01556
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of receptor and sensor proteins with novel functions

Abstract: The formation of complexes between proteins and ligands is fundamental to biological processes at the molecular level. Manipulation of molecular recognition between ligands and proteins is therefore important for basic biological studies and has many biotechnological applications, including the construction of enzymes, biosensors, genetic circuits, signal transduction pathways and chiral separations. The systematic manipulation of binding sites remains a major challenge. Computational design offers enormous ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
477
1
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(486 citation statements)
references
References 26 publications
2
477
1
6
Order By: Relevance
“…Previous work has addressed many problems related to the design of improved protein-protein binding affinity, such as the design of stable protein folds 2-4 , binding pockets for peptides and small molecules [5][6][7] , altered protein-protein specificity [8][9][10][11][12] , and altered enzymatic activity [13][14][15] . The design of improved antigen-binding affinity has met with limited success, however [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has addressed many problems related to the design of improved protein-protein binding affinity, such as the design of stable protein folds 2-4 , binding pockets for peptides and small molecules [5][6][7] , altered protein-protein specificity [8][9][10][11][12] , and altered enzymatic activity [13][14][15] . The design of improved antigen-binding affinity has met with limited success, however [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Their applications are enormous, and enzyme design holds the promise to provide important impact in society areas like medicine (i.e. treatment of neurodegenerative diseases [2], design of therapeutically antibodies to bind tumor-associated antigenic determinants while maintaining a small immunogenicity, development of peptide-based vaccines), biotechnology (biosensors [3,4], biocatalysts with activity in non-natural environments) and bioremediation (design of enzymes that would reduce waste by-products and toxicity [5]). …”
Section: Introductionmentioning
confidence: 99%
“…[5] In parallel, numerous genome-sequencing projects and structural genomics initiatives provided huge data bases for the correlation of the amino acid sequence of a protein with its structure and function. The clever use of these data for the development of new algorithms resulted in the creation of artificial highaffinity receptors for non-natural ligands [6] and culminated recently in the design from scratch of a small protein with a novel folding topology. This completely artificial protein had all the hallmarks of a natural protein, while its crystal structure revealed that the three-dimensional structure was essentially as planned in the design.…”
Section: Protein Designmentioning
confidence: 99%